Impaired Clearance From the Brain Increases the Brain Exposure to Metoclopramide in Elderly Subjects. Issue 3 (14th October 2020) - Bauer, Martin; Bamminger, Karsten; Pichler, Verena; Weber, Maria; Binder, Simon; Maier‐Salamon, Alexandra; Tahir, Ammar; Jäger, Walter; Haslacher, Helmuth; Tournier, Nicolas; Hacker, Marcus; Zeitlinger, Markus; et al.
Abstract : The antiemetic and gastroprokinetic drug metoclopramide is a weak substrate of the blood‐brain barrier (BBB) efflux transporter P‐gp and displays central nervous system (CNS) side effects (i.e., extrapyramidal symptoms and tardive dyskinesia) caused by dopamine D2 receptor blockade in the basal ganglia. These side effects occur with a higher incidence in elderly people. We used positron emission tomography to assess the brain distribution of [ 11 C]metoclopramide in young ( n  = 11, 26 ± 3 years) and elderly ( n  = 7, 68 ± 9 years) healthy men both after administration of a microdose (9 ± 7 µg) and a microdose co‐injected with a therapeutic dose of unlabeled metoclopramide (10 mg). For both doses, elderly subjects had a significantly higher total volume of distribution ( V T ) of [ 11 C]metoclopramide in the basal ganglia than young subjects (microdose: +26%, therapeutic dose: +41%). Increases in V T (= K 1 / k 2 ) were caused by significant decreases in the transfer rate constant of [ 11 C]metoclopramide from brain into plasma ( k 2, microdose: −18%, therapeutic dose: −30%), whereas the distributional clearance from plasma into brain ( K 1 ) remained unaltered. This reduction in the clearance of [ 11 C]metoclopramide ( k 2 ) from the brains of elderly subjects may be caused by an age‐related decrease in the activity of P‐gp at the BBB and may contribute to the higher incidence of CNS side effects of metoclopramide in the aged population. Our data suggest that an age‐associated decrease in the clearance properties of the BBB may modulate the CNS effects or side effects of clinically used P‐gp substrates.